2012
DOI: 10.1186/1756-3305-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory/anti-fibrotic effects of the hepatoprotective silymarin and the schistosomicide praziquantel against Schistosoma mansoni-induced liver fibrosis

Abstract: BackgroundPraziquantel (PZQ) is an isoquinoline derivative (2-cyclohexylcarbonyl-1, 2, 3, 6, 7, 11b-hexahydro-4H-pyrazino{2,1-a}-isoquinoline-4-one), and is currently the drug of choice for all forms of schistosomiasis. Silymarin, a standardized milk thistle extract, of which silibinin is the main component, is known for its hepatoprotective, anti-inflammatory, antioxidant activities, and hepatocyte regeneration. This study investigates the anti-inflammatory/anti-fibrotic effects of silymarin and/or PZQ on sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
75
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 47 publications
17
75
1
Order By: Relevance
“…These results agreed with the previous studies (Mata-Santos et al 2010;Rabia et al 2010;El-Lakkany et al 2012). Using Silymarin as an antifibrotics drug can inhibit hepatic stellate cells activation that subsequently reduced the production of extracellular matrix components and slow down the progression of liver fibrosis (Afdhal and Nunes 2004;Wu et al 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results agreed with the previous studies (Mata-Santos et al 2010;Rabia et al 2010;El-Lakkany et al 2012). Using Silymarin as an antifibrotics drug can inhibit hepatic stellate cells activation that subsequently reduced the production of extracellular matrix components and slow down the progression of liver fibrosis (Afdhal and Nunes 2004;Wu et al 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Silymarin, a standardized milk thistle extract, of which silibinin is the main component, is known for its hepatoprotective and promotes protein synthesis that helps in hepatocyte regeneration (El-Lakkany et al 2012). This effect could be attributed to its role as an antioxidant, antifibrotic, and antiinflammatory/immunomodulatory agent (Mata-Santos et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, silymarin was demonstrated to be capable of reducing transforming growth factor ␤1 (TGF-␤1) at the acute phase and the number of mast cells in mice infected with S. mansoni (42). The authors associated the silymarin-induced reduction of fibrosis with a reduction in the levels of TGF-␤1 in serum.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that other antioxidants also have the ability to prevent schistosomiasis-induced fibrosis when adminis- tered in the acute phase (4,5). El-Lakkany and coworkers (2012), treating infected mice with silymarin from 84 to 126 dpi, observed a slight decrease in the parasite burden and then in fibrosis, but the effect was smaller than that of praziquantel alone and possibly secondary to the decrease in burden (42). Herein, we did not observe alterations in the deposition of eggs in liver and intestinal tissues, which could suggest that there is no difference in parasite burden.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects included nausea and vomiting, neuropathy, diabetes and pancreatitis that all of them in the control group were higher and pancreatitis was not observed in the case group. It should be noted that about the side effects of Silymarin, particularly its longterm side effects, some studies have been conducted but further studies are recommended about it [11][12][13][14]. Hosseini et al in a study showed that treatment with Silymarin in patients with type II diabetes have had significant effects on gylcemic parameters improvement of the patients which also in the present study the FBS values in Silymarin group were significantly decreased compared to the control group.…”
Section: Discussionmentioning
confidence: 52%